2009
DOI: 10.1007/s11295-009-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of two novel complete Ty1-copia retrotransposons from apple and demonstration of use of derived S-SAP markers for distinguishing bud sports of Malus domestica cv. Fuji

Abstract: Retrotransposon-based molecular markers are a powerful tool for mapping and diversity studies. The scarcity of retrotransposon long terminal repeat (LTR) sequences limits the application of retrotransposon-based molecular marker systems. Here, we isolated two novel complete Ty1-copia retrotransposons (CTcrm1 and CTcrm2) in apple using a genome walking strategy. The CTcrm retrotransposons are nearly 5 kb long, and they have all the features of Ty1-copia retrotransposons. The differences in gene organization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 63 publications
(87 reference statements)
1
16
0
Order By: Relevance
“…1). Only retrotransposon markers were possible to distinguish spontaneous mutations (Venturi et al 2006;Zhao et al 2010). We also found no differences between cvs Belrené and King of Pippins, Mantet and Glencross, Red Spur Delicious, Starkrimson Delicious and Delicious Richared, respectively (Fig.…”
Section: Resultssupporting
confidence: 50%
“…1). Only retrotransposon markers were possible to distinguish spontaneous mutations (Venturi et al 2006;Zhao et al 2010). We also found no differences between cvs Belrené and King of Pippins, Mantet and Glencross, Red Spur Delicious, Starkrimson Delicious and Delicious Richared, respectively (Fig.…”
Section: Resultssupporting
confidence: 50%
“…The predicted amino acid sequences encoded by gag and pol of CTcrm1 and CTcrm2 show high homology to those of Tnt1, Tto1, TLC1.1, and CIRE1 (Zhao et al 2010). In our phylogenetic analysis, Ppcrt and CTcrm were both classified as copia-type elements but were subdivided into different groups (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…These systems have been successfully used for fingerprinting (Bretó et al 2001;Venturi et al 2006), linkage analysis and mapping of agronomic traits (Manninen et al 2000;Bernet and Asíns 2003), and analysis of genome evolution and genetic diversity (Ellis et al 1998;Kalendar et al 2000;Berenyi et al 2002;Soleimani et al 2005;Sanz et al 2007;Natali et al 2007;Yang et al 2007). The retrotransposon marker systems have been especially useful for bud sport identification in fruit crops (Bretó et al 2001;Venturi et al 2006;Zhao et al 2010). To carry out SSAP, primer sequences are necessary to specifically complement the terminal sequence of an LTR retrotransposon, most of which is complementary to the start of the LTR region .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MAS is essential, genome-wide polymorphism analyses and the development of reliable markers have been limited by the time-consuming and labor-intensive process. An attempt was made to identify 'Fuji' bud sports by retrotransposon-based sequence-specific amplified polymorphism markers (Zhao et al, 2010), but a lack of reproducibility indicated a methodological problem.…”
Section: Introductionmentioning
confidence: 99%